Cultural and Pathogenic Variability among the Isolates of Sclerotium rolfsii Causing Stem Rot of Chilli (Capsicum annuum L.) - Naresh, Prem; Ratan, Ved; Biswas, S. K.; Kumar, Virendra; Kumar, Upesh (International Journal of Bio-resource and Stress Management, 2023)
Variability among ten isolates of S. rofsii collected from different locations of chilli host is reported during 2009–10 and 2010–11 and these isolates varied in different Cultural characters likes’ colony diameter, no. of slerosia plate-1, colony character (colony appearance and colony colour) and sclerotial behaviar. In cultural variability, out of ten isolates of S. rofsii have revealed that maximum mycelial growth of 88.0 mm. was obtained on SR1 (Sarsaul) isolate followed by SR9 (Maudaha) isolate which was statistically at par with each other. The lowest mycelial growth of 79.0 mm was recorded in SR6 (Kucharia) isolate. It has also found that most of the isolates were produced sclerotia on large scale (>400 sclerotia plate-1), while some isolates were produced <300 sclerotia plate-1. The colony appearance from fluffy (SR1, SR2, SR3, SR4, SR8, SR9 and SR10) to compact (SR5, SR6 and SR7) while colony colours were dark brown, the sclerotial shapes were round while colours of sclerotia were light brown (SR1, SR2, SR3 and SR4) to dark brown (SR5, SR6 and SR7) and brown (SR8, SR9 and SR10). Sclerotial patterns were scarred to and groups. In pathogenic variability, among the ten isolates were also exist among the isolates representing the incidence of stem rot was recorded after one month of seedling 33.33–57.57% seedling mortality. The highest mortality (57.57%) was recorded in the isolates of (SR1) Sarsaul, Kanpur location and minimum 33.33% in the isolates of (SR5) Mallavan district, Hardoi.